Pengaruh Pembelajaran Matematika Dengan Menggunakan Media Video Pembelajaran Terhadap Kemampuan Penalaran Matematika Siswa - Lestari, Dian; Nurlita, Maya; Muhlis, Veny Mustianingsi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
The formulation of the problem in this study was whether there was an effect of learning mathematics using instructional video media on the mathematical reasoning abilities of eighth grade students of SMP Negeri 2 Baubau. The purpose of this study was to determine the effect of learning mathematics using instructional video media on the mathematical reasoning abilities of eighth grade students of SMP Negeri 2 Baubau. This research is quantitative research with experimental method and pretest-posttest research design. The data in this study were conducted using a research instrument in the form of an essay test given at the beginning and end of the treatment. The results of descriptive analysis of data on Class VIII students of SMP Negeri 2 Baubau, obtained in the experimental class with learning treatment using mathematics learning videos before and after giving the students' Mathematical reasoning test, the mean value was 61.42; median 60.00; mode 100; standard deviation 23.082; variance 53; minimum 20; and a maximum of 100. So based on the average results of mathematical reasoning using the t-test, it shows that learning mathematics by using learning videos has a significant positive effect on the mathematical reasoning of class VIII students of SMP Negeri 2 Baubau.